1994
DOI: 10.1002/tera.1420490410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coniine on the developing chick embryo

Abstract: Coniine, an alkaloid from Conium maculatum (poison hemlock), has been shown to be teratogenic in livestock. The major teratogenic outcome is arthrogryposis, presumably due to nicotinic receptor blockade. However, coniine has failed to produce arthrogryposis in rats or mice and is only weakly teratogenic in rabbits. The purpose of this study was to evaluate and compare the effects of coniine and nicotine in the developing chick. Concentrations of coniine and nicotine sulfate were 0.015%, 0.03%, 0.075%, 0.15%, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Coniine (2) is an agonist at fetal muscle-type nAChRs; racemic coniine has an approximate EC 50 of 200 lM in TE-671 cells (Table 1). Coniine (2) ingestion is associated with MCC in livestock species (Panter et al, 1988), but only to a limited extent in rabbits and not in rats (Forsyth and Frank, 1993;Forsyth et al, 1994). Interestingly, two pregnant mares orally dosed gestational days 45-75 with 15.5 mg/kg body weight coniine (2) in the form of dried ground poison hemlock exhibited signs of acute intoxication but their offspring were normal (Keeler et al, 1980).…”
Section: Coniine (2)mentioning
confidence: 99%
“…Coniine (2) is an agonist at fetal muscle-type nAChRs; racemic coniine has an approximate EC 50 of 200 lM in TE-671 cells (Table 1). Coniine (2) ingestion is associated with MCC in livestock species (Panter et al, 1988), but only to a limited extent in rabbits and not in rats (Forsyth and Frank, 1993;Forsyth et al, 1994). Interestingly, two pregnant mares orally dosed gestational days 45-75 with 15.5 mg/kg body weight coniine (2) in the form of dried ground poison hemlock exhibited signs of acute intoxication but their offspring were normal (Keeler et al, 1980).…”
Section: Coniine (2)mentioning
confidence: 99%
“…The substances pass through the shell membrane for absorption by the vitelline plexus underlying the air sac. This method greatly reduces mortality caused by piercing the vitelline membrane and has been used successfully in several teratological experiments by HASHIZUME et al (1992), FORSYTH et al (1994), VORSTER et al (1995 and HEYNS (1997).…”
Section: Methodsmentioning
confidence: 99%
“…The remaining two embryos from the groups had significant malformations however, due to the small sample size, a valid determination could not be made regarding nicotine-induced developmental malformations [3]. Forsyth et al [26] also observed mortality in nicotine-treated embryos in a dose-dependent manner with 1%, 5%, and 10% nicotine sulfate solutions producing a mortality rate of 37%, 67%, and 100%, respectively. Exposure of embryos at 48h incubation to 1 mg of nicotine caused a high incidence of embryonic death [27].…”
Section: Lower Survival Ratementioning
confidence: 99%
“…Nicotine is also a known stimulant on cholinoceptors which produces a depolarization blockage in skeletal muscles and ultimately causes paralysis [30]. Forsyth et al [26] observed embryonic movements for a 5-minute interval, one hour after nicotine administration, and found no movement in the treated embryos. Hamamichi and Nishigori [30] also observed complete stoppage, possibly paralytic, of swing-like movements in embryos treated with 10μg of nicotine and 1 x ACSE (aqueous cigarette smoke extract).…”
Section: Embryonic Movements and Malformationsmentioning
confidence: 99%